A Prospective Study of Diagnosis and Management Options of Chronic Pancreatitis in a Tertiary Care Hospital - Dr.C.Murali; Dr M. Yashica (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Constant inflammation and irreversible pancreatic tissue destruction are hallmarks of the disease of chronic pancreatitis, which results in the gradual loss of both exocrine and endocrine function. It is a multifactorial disease, with a wide range of symptoms and geographic variation. The incidence of chronic pancreatitis in the western population ranges from 8 to 10 cases yearly per 100,000 population, and the overall prevalence is 27.4 per 100,000 per year. According to a recent survey conducted in various countries in the Asia-Pacific region, chronic pancreatitis is prevalent in Southern India, with 114-200 cases per 100,000 people. In the Indian subcontinent, there has been no systematic nationwide study on the management of clinical profiles. Materials and Methods: Patients with malignant lesions of pancreas with chronic pancreatitis were included in the study. 100 cases of chronic pancreatitis, prospectively with an average follow up of 1 year from March 2024 to February 2025 (1 year). Data collection was done by collecting chronic pancreatitis cases from hospital database. The case files of all these patients were studied in detail regarding the onset and duration of the disease, pain status at time of acute onset, alcohol history, analgesic requirements, exocrine and endocrine dysfunction and number of hospital admissions. Investigations and interventions details were noted. Questionnaire for pain scoring was prepared. All the patients were called back to hospital and were asked to fill questionnaire. Results: A total of 100 patients were studied prospectively in a tertiary care hospital in North India with a follow up of 1 year. Male patients were 90 (60%), females were 60 (40%). Out of 100 patients, 15 (15%) were 30-40 years, 27 (26.6%) were 41-50 years, 51(34%) were 51-60 years, 21 (14%) were 61-70 years, 15 (10%) were ≥71years. Conclusion: Surgical methods gives superior results when compared with conservative method in management of chronic pancreatitis. It leads to improvement in endocrine function and improvement in exocrine function. So, patients with chronic pancreatitis should be offered surgery if there is persistent pain and deterioration of pancreatic functions.